The Influence of E-WOM Source Credibility in Beauty Product Reviews Containing Shopee Affiliate Links on Consumer Trust - Nabila, Yasmin; Wulandari, Astri (eProceedings of Management, 2025)
Indonesia's strong interest in online shopping encourages Shopee to develop the Shopee Affiliate Program as amarketing communication strategy. Shopee affiliate links are commonly used in beauty product reviews on the@ohmy_beautybank autobase account. The objective of this study was to analyze the influence of e-WOM sourcecredibility in beauty product reviews containing Shopee affiliate links on consumer trust. This study utilizes descriptivequantitative approaches. The probability sampling approach, specifically simple random sampling, is used to obtainresearch samples with the Slovin formula which generated 400 respondents. The research instrument proved validand reliable, and the data was analyzed by employing normality, heteroscedasticity, correlation, determinationcoefficient, and simple linear regression tests. The findings revealed that e-WOM source credibility in beauty productreviews containing Shopee affiliate links had a positive and significant influence on consumer trust. The correlationtest result of 0.827 indicates a very strong correlation between the two variables. The coefficient of determination testresults revealed that the e-WOM source credibility can explain or predict consumer trust by 68%, the remaining 32%explained by factors not examined in this study. This research can contribute theoretically to academic literature andpractically for Shopee affiliate users in increasing consumer trust.Keyword: Affiliate Marketing, Consumer Trust, E-WOM Source Credibility, Shopee